Nurses’ competency on use of metered dose inhaler - Rajbanshi, L; KC, S (Journal of Chitwan Medical College, 2017)
Inhalation therapy is the most recommended and effiecient therapy for Bronchial Asthma and Chronic Obstructive Pulmonary Disease. Its therapeutic effect depends upon the competent inhaler technique.Thus the objective of this study was to findout the Nurses’competemcy on use of Metered-Dose Inhaler(MDI). Nurses working in emergency, intensive care unit and medicine wards and interested to participate in the study were selected as samples. They were asked to demonstrate the steps in placebo MDI and skill was measured with 9 steps observation checklist. Out of 50 respondents, majority (94%) were of age group 19-22 years old. None of them had edequate competency in use of MDI. Mean technical score was 3.72 . Only 6% of nurses performed most difficult and essential step that is to breath deeply and slowly during actuation. Nurses have poor competency in MDI use. Therefore formal inservice training on MDI use is elemental.